Design and evaluation of selective butyrylcholinesterase inhibitors based on Cinchona alkaloid scaffold - Bosak, Anita (PLoS One, 2018)
This paper describes the synthesis and anticholinesterase potency of Cinchona-based alkaloids; ten quaternary derivatives of cinchonines and their corresponding pseudo-enantiomeric cinchonidines. The quaternization of quinuclidine moiety of each compound was carried out with groups diverse in their size: methyl, benzyl and differently meta- and para-substituted benzyl groups. All of the prepared compounds reversibly inhibited human butyrylcholinesterase and acetylcholinesterase with K(i) constants within nanomolar to micromolar range. Five cinchonidine derivatives displayed 95–510 times higher inhibition selectivity to butyrylcholinesterase over acetylcholinesterase and four were potent butyrylcholinesterase inhibitors with K(i) constants up to 100 nM, of which N-para-bromobenzyl cinchonidinium bromide can be considered a lead for further modifications and optimizations for possible use in the treatment of neurodegenerative diseases.